Duodenal Obstruction from Congenital Bands: An Unusual Cause of Pancreatitis - JD Just; RJ Bailey (Canadian Journal of Gastroenterology)
Acute pancreatitis in children has many different causes. An unusual case of pancreatitis is presented, along with a review of some of the factors associated with pancreatitis in children. The probable pathogenesis of pancreatitis in this case is also discussed.